The new French-English dictionary of slang and colloquialisms - Marks, Joseph; Marks, Georgette A.; Farmer, Albert John. (New York : E. P. Dutton, 1971)
This French dictionary contains what is hoped to be a far-reaching and, at the same time, a judicious selection of popular words and phrases with appropriate English renderings.
First published in London (1970) under title: Harrap's French-English dictionary of slang and colloquialisms.
ne 25/08/2021
Ref.
Keywords: French language